Gestão democrática e participação pedagógica: princípios do conhecimento e a práxis para um ensino de qualidade - Silva, Rita Rosana Braga da (2012)
The issue of Educational Participation and Democratic Management is an inexhaustible field for investigation of the educator. This is because many concepts are related to this theme, such as principles of knowledge, ideology, and dialogue. On the other hand one can not discuss the subject without regard to liberating education and awareness as critical pillars necessary to transform reality. In this sense the present work draws attention of educators to take their pedagogical identity. This implies the empowerment, the epistemological curiosity to achieve the desired practice. Struggles and calls up the challenge in this dissertation to all managers regarding the achievement of its goals by READING KEY (Knowledge, Skills, Attitudes, Values and Spirituality), actual working conditions.